2015
DOI: 10.4236/psych.2015.63024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Rotational Movement Difference and Handwriting Position on Academic Achievement and Learning Disabilities

Abstract: Only recently has movement behavior and learning disabilities (LD), including the confusing topic of dyslexia, been considered to be connected. The realization that phonemic problems may often be the "result" of learning issues such as dyslexia, and not the cause, has finally surfaced. This condition is hypothesized as being primarily due to not sensing the sound connection because of the hand feeling the shape of feeling letters incorrectly. This consequently, interferes with the sound value(s) being connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These authors’ findings showed that dysgraphia was significantly associated with a high incidence of motor impairments and the presence of minor neurological dysfunction (MND), suggesting a disturbance of the motor pathway, which has never been explored and is confused with motor coordination disorder in all DCD studies 10 , 11 , who highlighted MND among subjects presenting poor handwriting. Only a few authors 12 have studied certain isolated patterns, such as the way the pencil is handled or grasped, or the hand and/or wrist position when writing, but never gestural coordination. Indeed, studies on handwriting among school children were mainly interested in the spatio-temporal and kinematics of producing letters or words with digitizing tablets to write with a stylus on the screen or directly with a paper on the screen, seeking to identify the motor processes of handwriting in terms of spatial and temporal performances (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These authors’ findings showed that dysgraphia was significantly associated with a high incidence of motor impairments and the presence of minor neurological dysfunction (MND), suggesting a disturbance of the motor pathway, which has never been explored and is confused with motor coordination disorder in all DCD studies 10 , 11 , who highlighted MND among subjects presenting poor handwriting. Only a few authors 12 have studied certain isolated patterns, such as the way the pencil is handled or grasped, or the hand and/or wrist position when writing, but never gestural coordination. Indeed, studies on handwriting among school children were mainly interested in the spatio-temporal and kinematics of producing letters or words with digitizing tablets to write with a stylus on the screen or directly with a paper on the screen, seeking to identify the motor processes of handwriting in terms of spatial and temporal performances (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is why these otherwise generally intelligent students have such difficulty learning the written word and attending to the task. This is also why these students are so often misunderstood, and why teachers find it so difficult for these students to successfully develop written language proficiency (Young, 2015). However, research is now "showing that letter perception is facilitated by handwriting experience, further suggesting that handwriting fluency is important for letter processing in the brain".…”
Section: Description Of Reverse Positioning Sensationmentioning
confidence: 99%